EVALUASI IMPLEMENTASI DESAIN PENDIDIKAN KARAKTER BERBASIS PENDEKATAN HUMANISTIK - Musyarrafah Sulaiman Kurdi (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2018)
The purpose of this study is to provide an illustration of the implementation resultof the learning design of character education courses based on a humanistic approach. This approach is used in order to provide atmospheric process of learning activities by providing stimulus to students as subjects in the learning process to acquire skills, knowledge, values and attitudes that are able to bring self-awareness as a person. Previously, researcher have conducted development research to produce design of character education course based on humanistic approach. In this study, the research method used was a survey, in which researcher cited describing the results of the implementation of the learning process in the character education course based on a humanistic approach at UIN Antasari Banjarmasin in 2017 majoring in Islamic Madrasah Teacher Education, with 72 samples. Based on the results of the study, it is known that the design of character education courses based on the humanistic approach that has been designed previously, it is known that in 5 times learning processes, 75% of students feel that they have experienced the development of their inner values, 80% feel that each of them knows themselves more deeply than the past, and 87% felt that they had a clearer purpose in life, and 89% said that their inner potential could be more explored and more deep after do sequence of value project and activities. In general, there is an increase values and attitudes in students by 40%, to 75% -89%, where previously only at the percentage of 35-63%.